Promosi Sekolah Melalui Penerapan Branding School Di TKIT Sakinah Arga Makmur - Sumarsih; Nur Anisah (UNIVERSITAS BENGKULU, 2023)
Promotion is an annual agenda for almost all schools, so that promotion gets maximum results schools need to do branding. The general objective of this research is to describe the application of branding school as a school promotion in Sakinah Arga Makmur Integrated Islamic Kindergarten including, branding strategy, implementation steps and supporting factors as well as inhibiting factors. This research uses qualitative methods with data collection techniques through interviews, observation and documentation studies. The results of the study show that branding strategies are carried out through school identity, excellent service programs, increasing student achievement, and publication through social media. A series of strategic steps in implementing school branding is a new way of promoting profitable schools.